MEDINA-VICENT, Maria (2020). Mujeres y discursos gerenciales. Hacia la autogestión feminista. Granada: Comares. - García-Granero, Marina (Daimon Revista Internacional de Filosofia, 2022)
Reseña de: MEDINA-VICENT, Maria (2020). Mujeres y discursos gerenciales. Hacia la autogestión feminista. Granada: Comares.